ANALISIS FAKTOR JUMLAH PRODUKSI IKAN OLAHAN DI KELURAHAN PASIE NAN TIGO KOTA PADAN - Jefri Irawan; Junaidi Junaidi; Zaitul Zaitul (JURNAL PUNDI, 2022)
The purpose of this study was to analyze the factors that influence the creativity of fish processors in Pasia Nan Tigo Village, Koto Tangah District, Padang City. This type of research uses quantitative research using survey research methods. The data analysis method used was multiple linear regression with independent variables namely Motivation, Interests, Creativity Attitudes and Processing Facilities/Equipment with the dependent variable being the amount of processed fish production. The results showed that the factors that influence the creativity of fish processors in Pasia Nan Tigo Village are motivational factors with a t-count value of 2.223 > t-table 2.05183 and an interest factor seen by a t-count value of 2.122 > 2.05183. The results of the F test also show that the calculated F is greater than the F table 23.555 > 2.73. The value of the coefficient of determination (R2) Adjusted R Square shows that 74.4 percent of processed fish production variables can be explained by the variables of Motivation, Interests, Creativity Attitudes and Processing Facilities/Equipment. While 25.6 percent is influenced by other variables not included in the mode regression.